CHEMICAL COMPOSITION, ANTIHYPERTENSIVE ACTIVITY AND IN VIVO TOXICITY OF LEAVES EXTRACTS OF TWO BENINESE MEDICINAL PLANTS - TOKOUDAGBA, Kossi Jean-Marie Denis; ADJAGBA, Marius; Gandonou, Clément; Awede, Bonaventure; LALEYE, OLABISSI ANATOLE A. (My University, 2018)
The characterization of chemical constituents of alcohol-water extracts of Parkia biglobosa and Spondias mombin leaves revealed the presence of the following two important chemical groups: catechical tannins, reducing compounds and mucilage. Gallic tannins, flavonoids, leucoanthocyans, combined anthracenic derivatives (C-Heterosids), coumarin are found only in Parkia biglobosa leaves and saponosids are present only in Spondias mombin leaves. The alcohol-water extracts of Parkia biglobosa and Spondias mombin revealed in vivo an anti-hypertensive action respectively 171 mm Hg to 143 mm Hg, and 171 mm Hg to 154 mm on the rats whose blood pressure is higher than normal provoked by the L-NAME at the dose of 20mg/Kg/J. The anti-hypertensive effect of Parkia biglobosa crude extract is more important than the one of Spondias mombin crude extract. The study of acute toxicity of the two extracts carried out on NMRI mice allowed to classify these two species in the class III of World Health Organization (WHO): class of slightly toxic extracts with a lethal dose (LD 50 limit) higher than 2000mg/Kg
Keywords: Parkia biglobosa; Spondias mombin; alcohol-water extract; anti-; hypertensive activity; toxicity.